THE ROLE OF THIRD PARTY FUNDS ON DISTRIBUTION OF WORKING CAPITAL LOANS AND INCOME AT PT BANK SULSELBAR MAROS BRANCH - Wairooy, Mohamad Ali; A.R, Andi Fitriya (Jurnal Ekonomi Balance, 2019)
The purpose of this study was to determine the role of third party funds in the distribution of working capital loans and income at PT Bank Sulselbar Maros Branch. The type of research used is descriptive qualitative where the author describes the results of observations and analyzes based on 2016-2018 data obtained in the field. The writing of this final project is the result of research conducted at PT Bank Sulselbar Maros Branch. After conducting research and analyzing the discussion, it was found that: 1) Third party funds play an important role in the distribution of working capital loans; 2) The purpose of capital credit is to assist the business of individual customers or business entities that need funds to expand their business; 3) PT Bank Sulselbar Maros Branch earns income from interest on placement of third party funds with other banks, income from loan interest and income from Fee Based Income.